Argonaute proteins regulate HIV-1 multiply spliced RNA and viral production in a Dicer independent manner - Eckenfelder, Agathe (Nucleic Acids Res, 2017)
Argonaute (Ago) proteins associate with microRNAs (miRNAs) to form the core of the RNA-induced silencing complex (RISC) that mediates post-transcriptional gene silencing of target mRNAs. As key players in anti-viral defense, Ago proteins are thought to have the ability to interact with human immunodeficiency virus type 1 (HIV-1) RNA. However, the role of this interaction in regulating HIV-1 replication has been debated. Here, we used high throughput sequencing of RNA isolated by cross-linking immunoprecipitation (HITS-CLIP) to explore the interaction between Ago2 and HIV-1 RNA in infected cells. By only considering reads of 50 nucleotides length in our analysis, we identified more than 30 distinct binding sites for Ago2 along the viral RNA genome. Using reporter assays, we found four binding sites, located near splice donor sites, capable of repressing Luciferase gene expression in an Ago-dependent manner. Furthermore, inhibition of Ago1 and Ago2 levels in cells expressing HIV-1 led to an increase of viral multiply spliced transcripts and to a strong reduction in the extracellular CAp24 level. Depletion of Dicer did not affect these activities. Our results highlight a new role of Ago proteins in the control of multiply spliced HIV-1 transcript levels and viral production, independently of the miRNA pathway.